Macrophage modulation in activation process induced immune thrombocytopenia - Mahdaleny, Mahdaleny; Bustami, Arleni; Iswanti, Febriana Catur (Universa Medicina, 2024)
The immune system operates like an orchestra that harmoniously maintains the homeostasis balance while protecting from external or internal pathogens attack. Inflammation is one of the key critical immune defenses to eradicate pathogens and encourage tissue repair and recovery by activating the host’s immune and non-immune cells. As a part of the immune response during inflammation, blood platelets serve various functions; however, their activation and involvement in inflammation can also contribute to pathological conditions, such as thrombosis, which results in myocardial infarction, stroke, and venous thromboembolism. Activated platelets can mobilize and release intracellular granules (alpha and dense granules), which include secondary mediators like chemokine PF4/CXCL4. In contrast to most other chemokines, PF4 participates in several long-term regulatory processes, such as cell differentiation, survival, and proliferation. However, recent findings suggest that PF4 is also responsible for modulating macrophage polarization, which can substantially impact the development of induced immune thrombotic thrombocytopenia. This review aims to explain how PF4 induced vascular problems by modulation of macrophage development during immunological thrombocytopenia. A literature search using the keywords PF4, CXCL4, macrophage M4, platelet macrophage M4, and induced immune thrombocytopenia was done using the following databases: Google Scholar, ProQuest, ScienceDirect, and Scopus for articles published from 2000 to 2023. The literature study was done to find the connection between platelet activation, macrophage modulation, and vascular problems such as atherosclerosis and thromboembolism in induced immune thrombotic thrombocytopenia. Several recent studies on PF4, macrophage modulation, and vaccine-induced thrombotic thrombocytopenia were carefully reviewed. This review concludes that macrophage polarization modulation is promising in managing vascular problems in patients with induced immune thrombotic thrombocytopenia.